Future directions for reproductive coercion and abuse research - Karen Trister Grace; Elizabeth Miller (BMC, 2023)
Abstract Background Reproductive coercion and abuse (RCA) is a form of intimate partner violence (IPV) in which people with the capacity for pregnancy experience coercive behaviors that threaten their reproductive autonomy. Behaviors that constitute RCA include contraceptive control/sabotage, pregnancy pressure, and controlling the outcome of a pregnancy. Summary Several areas of RCA study have emerged: associations with IPV, health outcomes resulting from RCA, and demographic and contextual factors associated with experiencing RCA. Current research in these areas is summarized and placed in a global context, including sexual and gender minority groups, use of RCA (exploring perpetration), RCA interventions, RCA in women with disabilities, and the question of whether people assigned male at birth can be RCA victims. Conclusion Areas for future exploration include evolving interpretations of pregnancy intention in the setting of fewer options for abortion, RCA in people with disabilities and multiple levels of marginalization, including sexual and gender minorities; intersections between RCA and economic abuse in the context of efforts at economic justice; and community-centered approaches to intervention and prevention.